Utilization of Fermented Eucheuma cottonii Flour in Feed for Cultivation of Tilapia (Oreochromis niloticus) - Salnida Yuniarti Lumbessy; Fadlatul Anami; Dewi Putri Lestari (Barakuda'45, 2022)
This study heads to analyze the effect of adding fermented E. cottonii flour as raw materials on the growth and survival rate of tilapia. The method used in this study is an experimental method with a Completely Randomized Design (CDR) using 4 treatments and 3 replications. The treatments tested consisted of 0% E. cottonii flour (P1/Control), 4% fermented E. cottoni flour ( P2), 8% fermented E. cottoni flour (P3), 12% fermented E. cottoni flour (P4). Parameters observed were specific growth rate, absolute weight growth, absolute length growth, feed conversion, feed efficiency and tilapia fry survival. Data were analyzed using analysis of variance (ANOVA) with 95% confidence level. The results showed that the addition of E. cottonii seaweed flour fermented by tape yeast in the feed formulation could affect the efficiency of feed utilization but did not affect the growth, feed conversion and survival rate of tilapia. The addition of E. cottonii flour fermented by tape yeast to a concentration of 8% (P3) gave the best results because it could increase the efficiency of tilapia feed by 71.16% to 73.9%.